An adaptive rate allocation system to mitigate fairness issues in Wi-Fi mesh networks - Torshizi, Seyed Dawood Sajjadi (2013)
Wireless Mesh Network (WMN) is a high potential networking technology that is equipped with self-healing and self-organized capabilities. In addition to being widely used in the traditional applications of ad-hoc networks, WMNs are under-going rapid commercialization in many other scenarios such as broadband home and community networking, high-speed metropolitan area networks, and enter-prise networking. To this date, a rich surge of researches involving deployments with thorough solutions have been conducted on WMNs. However, fair distribu-tion of network resources,especially the available bandwidth among mesh stations is still one of the open issues for research. In WMNs, stations which are more hops away from the gateway generally sufer from higher throughput degradation and hence higher delay. Moreover, current fairness issues among simultaneous up-link and downlink ows of WLANs aggravate starvation dilemma in access layer of WMNs. These incidents are mainly due to the unpredictable nature of IEEE 802.11 protocol and its operation in contention mode. In this dissertation, a thorough solution based on a messaging framework and adaptive rate allocation mechanism is proposed to alleviate current fairness issues of WMNs. The proposed framework consists of two main components. The first one is a lightweight messaging system and the second one is an adaptive fair rate allocation algorithm. It is important to note that the presented solution is independent from MAC and underlying layers. Thus, this property distinguishes it from many other related works on addressing fairness problems in WMNs. Furthermore, the ability of trafic control over UDP and TCP streams, supporting multi-radio mesh routers and restriction of internal greedy trafic within WMNs can be regarded as the main advantages of the offered solution in comparison to the earlier works. The consistency of presented results from the algorithm simulation and real-life test-bed experiments substantiates the eficiency of proposed architecture in terms of achieving higher end-to-end through-put and fairness improvement more than 94% in some of the conducted scenarios. Furthermore, in the existence of any malicious activity such as UDP food or DoS (Denial of Service) attacks by mesh stations, it is feasible to block abusive users through definition of appropriate policies by the offered system. This capability enhances the stability of any communication platform which is working based on the presented solution to control and addressing users' demands.